Pilates training improves 5-km run performance by changing metabolic cost and muscle activity in trained runners - Finatto, P.; Soares Da Silva, E.; Okamura, A. B.; Almada, B. P.; Oliveira, H. B.; Peyre-Tartaruga, L. A. (PLOS ONE, 2018)
Strength training improves distance running economy and performance. This finding is based predominantly on maximal and explosive strength programmes applied to locomotor muscles, particularly on the lower limbs. It is not certain whether a minimization of metabolic cost (Cmet) and an improvement in running performance is feasible with strength training of the postural and trunk muscles. Methods: Using kinematic, neuromuscular and metabolic measurements of running at two different speeds before and after a 12-week Pilates training programme, we tested the hypothesis that core training might improve the running Cmet and performance of trained runners. Thirty-two individuals were randomly assigned to the control group (CG, n = 16) or the Pilates group (PG, n = 16). Results: Confirming our hypothesis, a significant improvement (p<0.05) was observed for running performance in the PG (pre: 25.65±0.4 min; post: 23.23±0.4 min) compared to the CG (pre: 25.33±0.58 min; post: 24.61±0.52 min). Similarly, the PG (4.33±0.07 J.kg-1.m-1) had better responses than the CG (4.71±0.11 J.kg-1.m-1) during post-training for Cmet. These findings were accompanied by decreased electromyographic activity of the postural muscles at submaximal running intensities in the PG. Conclusions: Overall, these results provide a rationale for selecting strength training strategies that target adaptations on specific postural and locomotor muscles for trained distance runners.